Prevalence of Intestinal Parasitic Infestations in School going Children of Udaya Kharka Secondary School, Chapagaun, Lalitpur, Nepal - Khadka, Damber; Butterworth, K. (Journal of Karnali Academy of Health Sciences, 2018)
Intestinal Parasitic infestation is major cause of childhood morbidity in developing countries like Nepal with lack of hygiene and safe water supply. This study was done to find the actual scenario of parasitic infestation in a population of Nepal. This cross sectional, prospective study was undertaken in Udaya Kharkha Secoundary School, Chapagaun, Lalitpur. The study population included 246 students from school of age 6 years to 18 years. Routine and microscopic examination was done for stool collected from healthy students. Children among examined incidence of infestation was 52%. And different six types of parasites were found. Among which Giardiasis was the common with 42%. There was high incidence of parasitic infestations in school going children in the school. Incidence of parasitic infestations according to sex showed that girls are infested more than boys and according to age group 11 to 14 years age group is highly infested.